Chosen aspects of medical care in Poland for patient from the Islamic culture - Chrzan-Rodak, Agnieszka; Bąk, Jadwiga; Machul, Michał; Bieniak, Monika; Chałdaś-Majdańska, Justyna; Dobrowolska, Beata (Journal of Education, Health and Sport, 2017)
Introduction. The progressing globalisation process creates new challenges for healthcare in Poland, which are related mainly providing cultural security for patients from different culture circles. Aim. The objective of the study is to analyse chosen aspects of medical care in Poland for patients from the Islamic culture. Methods. A qualitative, contextual analysis of the material from interviews conducted among five followers of Islam who live in Lublin. The survey was carried out from 20 June to 8 July 2016 at the Islamic Cultural Centre in Lublin. The process of sampling the representatives of Islamic culture involved the snowball sampling method. The interviews were recorded and transcribed. Results. The qualitative analysis of the data obtained made it possible to specify the following categories of issues related to care for patients representing the Islamic culture in nursing practice: prayer in the hospital environment, fasting in hospital conditions, meals in hospitals, care and nursing and the carer’s sex, treatment and medications, challenges in care for patients from different culture circles. Conclusions. The survey results show that religious practices, cultural differences related to meals, medications, selected medical and care procedures and communication are issues which require greater attention of medical personnel in the process of care for patients representing different cultures – in this case the Islamic culture. Patients from the Islamic culture staying in Polish hospitals are ready to adjust to the healthcare system and to seek alternative procedures enabling them to preserve their cultural identity. Developing the cultural competence of medical students and occupationally active medical professionals is an important issue aiming at protecting cultural safety of the patient.